Analisis Proses Pembelajaran Berbasis Student Centered Learning pada Mahasiswa Pendidikan Ekonomi STKIP PGRI Bandar Lampung - Mahrunnisya, Dyanti; Arga, Kharisma Idola; Ta'lim, Muhammad Alse (Lentera: Jurnal Ilmiah Kependidikan, 2024)
There is a gap between the knowledge that students have and their attitudes and behaviors. Having an understanding and being able to memorize material is something most students have, but the weakness is the difficulty of applying knowledge in everyday life. One of the causes is when the learning process does not use the right method / method / approach, such as the habit of using conventional methods and only focusing on concepts. Learning that focuses on an educator as the main source of learning is no longer relevant in learning activities today. The research was conducted on Economics Education students class of 2022 totaling 37 people. The data collection technique used a likert scale questionnaire. Furthermore, the data obtained were described using quantitative descriptive methods supported through data presentation in the form of pie chart diagrams to make it easier for readers to understand the results of the study. The results of the study explain that the learning process based on Student Centered Learning (SCL) is stated to be 1) able to arouse the courage to ask questions and present during the learning process, 2) improve the ability to guide learning from beginning to end, 3) SCL provides opportunities to apply technology-based learning resources and media, 4) SCL helps improve speaking skills in front of the class.